HUBUNGAN ANTARA KECERDASAN EMOSIONAL, KEMANDIRIAN DAN KREATIVITAS BELAJAR DENGAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS X SMA NEGERI 1 SUKAWATI - Ni Kadek Lia Wulandari; I Wayan Sudiarsa (FPMIPA IKIP PGRI Bali, 2016)
Relationship between Emotional Intelligence, Self-Learning and Creativity with Mathematic Learning Result of 10th Grade Students in SMA N. 1 Sukawati. This research aims to determine relationship between emotional intelligence, selflearning and creativity with mathematic learning result of 10th grade students in SMA Negeri 1 Sukawati. This research was korelational research. Population of this research were 381 students (10 classes) of 10th grade SMA Negeri 1 Sukawati. The technique of sampling was using multi stage random sampling which the classes that were randomized. The result of randomizing was obtained the research sample consisted of two classes (73 students). Data of emotional intelligence, self-learning and creativity were collected through the administration of questionnaires, while the data of mathematics learning outcomes was collected through the administration of evaluation tests on daily tests of mathematic. Data were analyzed using simple regression and multiple regression. The results showed that: 1). There was significant relationship between emotional intelligence with mathematic learning resultof 10th grade students in SMA Negeri 1 Sukawati. 2). There was significant relationship between self-learning with mathematic learning resultof 10th grade students in SMA Negeri 1 Sukawati. 3) There was significant relationship between creativity with mathematic learning resultof 10th grade students in SMA Negeri 1 Sukawati. 4) There were significant relationship between emotional intelligence, self-learning and creativity with mathematic learning resultof 10th grade students in SMA Negeri 1 Sukawati.